Response of the carotid artery longitudinal motion to submaximal physical activity in healthy humans—Marked changes already at low workload - Ahlgren, Åsa Rydén; Erlöv, Tobias; Cinthio, Magnus (Physiological reports, 2023)
The longitudinal motion of the arterial wall, that is, the displacement of the arterial wall along the artery, parallel to blood flow, is still largely unexplored. The magnitude and nature of putative changes in longitudinal motion of the arterial wall in response to physical activity in humans remain unknown. The aim of this study was therefore to study the longitudinal motion of the carotid artery wall during physical activity in healthy humans. Using in‐house developed non‐invasive ultrasonic methods, the longitudinal motion of the intima‐media complex and the diameter changes of the right common carotid artery (CCA) in 40 healthy volunteers (20 volunteers aged 22–35 years; 20 volunteers aged 55–68 years) were assessed at rest and during submaximal supine bicycle exercise. In a subset of the subjects (n = 18) also intramural shear strain were analyzed. The longitudinal motion of the intima‐media complex underwent marked changes in response to physical activity, already at low workload; with most evident a marked increase of the first antegrade displacement (p < 0.001) in early systole. Likewise, the corresponding shear strain also increased significantly (p = 0.004). The increase in longitudinal motion showed significant correlation to increase in blood pressure, but not to blood flow velocity or wall shear stress. In conclusion, physical activity markedly influences the longitudinal motion of the carotid artery wall in healthy humans already at low load. A possible “cushioning” function as well as possible implications for the function of the vasa vasorum, endothelium, and smooth muscle cells and extracellular matrix of the media, are discussed. The longitudinal motion of the arterial wall, that is, the displacement of the arterial wall along the artery, parallel to blood flow, is still largely unexplored. Using in‐house developed non‐invasive ultrasonic methods we show, for the first time, that physical activity markedly influences the longitudinal motion of the carotid artery wall in healthy humans already at low load. Possible implications for cardiovascular function are discussed.